2020
DOI: 10.3389/fnins.2020.00303
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of eEF1A/EFT3-4 Enhances Dopaminergic Neurodegeneration After 6-OHDA Exposure in C. elegans Model

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder characterized by the aggregation of α-synuclein protein and selective death of dopaminergic (DA) neurons in the substantia nigra of the midbrain. Although the molecular pathogenesis of PD is not completely understood, a recent study has reported that eukaryotic translation elongation factor 1 alpha (eEF1A) declined in the PD-affected brain. Therefore, the roles of eEF1A1 and eEF1A2 in the prevention of DA neuronal cell death in PD are aimed to be investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…In the transgenic BZ555 worms, the morphological pattern of dopamine neurons could be observed through the dopamine transporter protein DAT-1::GFP. Selective degeneration of dopamine neurons in C. elegans can be induced by 6-hydroxydopamine (6-OHDA) [ 67 ]. Our results showed that 6-OHDA decreased the average fluorescence intensity of dopamine neurons in the BZ555 worms from 48.418 to 20.168, while HBA treatment remained the average fluorescence intensity at 30.151 (Figures 2(c) and 2(d) ), suggesting that HBA treatment protected the degeneration of head neurons in BZ555 worms.…”
Section: Resultsmentioning
confidence: 99%
“…In the transgenic BZ555 worms, the morphological pattern of dopamine neurons could be observed through the dopamine transporter protein DAT-1::GFP. Selective degeneration of dopamine neurons in C. elegans can be induced by 6-hydroxydopamine (6-OHDA) [ 67 ]. Our results showed that 6-OHDA decreased the average fluorescence intensity of dopamine neurons in the BZ555 worms from 48.418 to 20.168, while HBA treatment remained the average fluorescence intensity at 30.151 (Figures 2(c) and 2(d) ), suggesting that HBA treatment protected the degeneration of head neurons in BZ555 worms.…”
Section: Resultsmentioning
confidence: 99%
“…Expressions of Bax and cleaved caspase 3 were increased while Bcl-2 expression was decreased in OGD-treated neurons after EEF1A2 overexpression and Perifosine treatment. EFF1A is pivotal in 6-OHDA-induced neurodegeneration via the PI3K/Akt/mTOR pathway [ 46 ]. Fangji decoction represses hippocampal neuron apoptosis by regulating the Akt/mTOR pathway in febrile seizures [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RNA samples were stored at −80 °C until use. The RNA concentration was quantified using NanoDrop 2000 Spectrophotometer (Thermo Scientific, Waltham, MA, USA) [ 61 ]. For quantitative gene expression analyses, high capacity complementary DNA (cDNA) was generated from 2 µg of RNA, using the iScriptTMReverse Transcription Supermix for RT–qPCR (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%